Assessing Voice Hearing in Trauma Spectrum Disorders: A Comparison of Two Measures and a Review of the Literature - Shinn, Ann K.; Wolff, Jonathan D.; Hwang, Melissa; Lebois, Lauren A. M.; Robinson, Mathew A.; Winternitz, Sherry R.; Öngür, Dost; Ressler, Kerry J.; Kaufman, Milissa L. (Frontiers in Psychiatry, 2020)
Voice hearing (VH) can occur in trauma spectrum disorders (TSD) such as posttraumatic stress disorder (PTSD) and dissociative disorders. However, previous estimates of VH among individuals with TSD vary widely. In this study, we sought to better characterize the rate and phenomenology of VH in a sample of 70 women with TSD related to childhood abuse who were receiving care in a specialized trauma program. We compared the rate of VH within our sample using two different measures: (1) the auditory hallucination (AH) item in the Structured Clinical Interview for DSM-IV-TR (SCID), and (2) the thirteen questions involving VH in the Multidimensional Inventory of Dissociation (MID), a self-report questionnaire that comprehensively assesses pathological dissociation. We found that 45.7% of our sample met threshold for SCID AH, while 91.4% met criteria for MID VH. Receiver operating characteristics (ROC) analyses showed that while SCID AH and MID VH items have greater than chance agreement, the strength of agreement is only moderate, suggesting that SCID and MID VH items measure related but not identical constructs. Thirty-two patients met criteria for both SCID AH and at least one MID VH item (“unequivocal VH”), 32 for at least one MID VH item but not SCID AH (“ambiguous VH”), and 6 met criteria for neither (“unequivocal non-VH”). Relative to the ambiguous VH group, the unequivocal VH group had higher dissociation scores for child voices, and higher mean frequencies for child voices and Schneiderian voices. Our findings suggest that VH in women with TSD related to childhood abuse is common, but that the rate of VH depends on how the question is asked. We review prior studies examining AH and/or VH in TSD, focusing on the measures used to ascertain these experiences, and conclude that our two estimates are consistent with previous studies that used comparable instruments and patient samples. Our results add to growing evidence that VH—an experience typically considered psychotic or psychotic-like—is not equivalent to having a psychotic disorder. Instruments that assess VH apart from psychotic disorders and that capture their multidimensional nature may improve identification of VH, especially among patients with non-psychotic disorders.